Numerical analysis on the crack propagation and failure characteristics of rocks with double fissures under the uniaxial compression - Leyong Chen; Jianjun Liu (Petroleum, 2015)
The fissures and rock bridges with different dips had different contributions to crack's initiation, propagation, convergence and penetration. In this paper, based on the rock fracture theory, the crack's propagation and evolution process on rock specimen with double fissures under uniaxial compression was simulated. As a result, the crack propagation and evolution law of rocks with different fissure dips (α = 0°, 15°, 30°, 45°, 60°, 75°, 90°; β = 45°) and different rock bridge dips (β = 0°, 30°, 45°, 60°, 90°; α = 45°) was obtained by numerical tests. Meanwhile, the fissure and rock bridge dips influence on the macro mechanical properties of rock was analyzed. Besides, the paper investigated the influences of different fissure dips and different rock bridge dips on the bridge transfixion. The study is of great significance to reveal the impact of different dips on the mechanical mechanism of multiple-fissures rock under specific conditions, and it also has important theoretical significance for the research on multiple-fissure rock.